RESEÑA de: Gutiérrez Gutiérrez, I (coord.); Alguacil González-Aurioles, J; Reviriego Picón, F; Salvador Martínez, M. Elementos de Derecho Constitucional Español. Madrid : Marcial Pons, 2014 - Fondevila Marón, Manuel (Revista de Derecho de la UNED (RDUNED), 2015)
-